Comparative Genome Analysis of Bacillus amyloliquefaciens Focusing on Phylogenomics, Functional Traits, and Prevalence of Antimicrobial and Virulence Genes - Liu, Hualin; Prajapati, Vimalkumar; Prajapati, Shobha; Bais, Harsh; Lu, Jianguo (Frontiers in Genetics, 2021)
Bacillus amyloliquefaciens is a gram-positive, non-pathogenic, endospore-forming, member of a group of free-living soil bacteria with a variety of traits including plant growth promotion, production of antifungal and antibacterial metabolites, and production of industrially important enzymes. We have attempted to reconstruct the biogeographical structure according to functional traits and the evolutionary lineage of B. amyloliquefaciens using comparative genomics analysis. All the available 96 genomes of B. amyloliquefaciens strains were curated from the NCBI genome database, having a variety of important functionality in all sectors keeping a high focus on agricultural aspects. In-depth analysis was carried out to deduce the orthologous gene groups and whole-genome similarity. Pan genome analysis revealed that shell genes, soft core genes, core genes and cloud genes comprise 17.09%, 5.48%, 8.96%, and 68.47%, respectively which demonstrate genomes are very different in the gene content. It also indicates that the strains may have flexible environmental adaptability or versatile functions. Phylogenetic analysis showed that B. amyloliquefaciens is divided into two clades and clade-II is further dived into two different clusters. This reflects the difference in the sequence similarity and diversification that happened in the B. amyloliquefaciens genome. The majority of plant-associated strains of B. amyloliquefaciens were grouped in Clade-II (73 strains), while food-associated were in Clade-I (23 strains). Genome mining has been adopted to deduce antimicrobial resistance and virulence genes and their prevalence amongst the all strains. The genes tmrB and yuaB codes for tunicamycin resistance protein and hydrophobic coat forming protein, which only exist in Clade 2, while clpP, which codes for serine proteases, is only in Clade 1. Genome plasticity of all strains of B. amyloliquefaciens reflects their adaption to different niches.